DEVELOPMENT OF DIGITAL-BASED TEACHING MATERIALS USING FLIPBOOK APPLICATION - Pakonglean, Grace; Liggih, I Ketut; Pratama, Muh. Putra (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2024)
SMA Negeri 7 Tana Toraja is a high school located in Bonggakaradeng District, Tana Toraja Regency. Printed teaching materials are used in the learning process of students without the use of technology that will increase students' insight so that students are still very monotonous and less interesting, this happens in class XI.2 in Informatics subjects, especially in the Social Impact of Informatics material. Therefore, it is necessary to develop digital-based teaching materials using a flipbook application in class XI.2. This study aims to (1) describe the need for the development of digital-based teaching materials using a flipbook application in class XI.2 of informatics subject at SMA Negeri 7 Tana Toraja, (2) find out the design of the development of digital-based teaching materials using a flipbook application in class XI.2 of informatics subject at SMA Negeri 7 Tana Toraja, (3) find out the level of validity and practicality of the development of digital-based teaching materials using a flipbook application in class XI.2 of informatics at SMA Negeri 7 Tana Toraja. The results of validation by media experts on digital-based teaching materials obtained a percentage of 84.44% in the